Recurrent pacemaker‐mediated arrhythmia with a right bundle branch block pattern in a patient with a cardiac resynchronization therapy device - Yubin Zhang; Yiru Han; Liangrong Zheng (Annals of Noninvasive Electrocardiology, 2023)
Abstract Under certain conditions, cardiovascular implantable electronic devices can be directly involved in initiating and sustaining pacemaker‐mediated arrhythmias (PMA), of which repetitive reentrant ventriculoatrial synchrony (RRVAS) is the most well‐known and common type. RRVAS, also known as pacemaker‐mediated tachycardia, was commonly secondary to atrioventricular (AV) dissociation and subsequent ventriculoatrial (VA) conduction. RRVAS in a biventricular system is rare due to its less predisposition to the appearance of AV dissociation and subsequent VA conduction, but urgent in its adverse impact on cardiac resynchronization therapy (CRT), which may predispose to exacerbated heart failure. We present a rare case of recurrent PMA manifested as a right bundle branch block pattern in a patient with a CRT device. Notably, most episodes of PMA were triggered by a premature atrial contraction accompanied by the appearance of VA conduction with no prolongation of AV delay. In this study, we have demonstrated the impact of the appearance of VA conduction due to the loss of capture of right ventricular lead and its potential risk for inducing RRVAS in a CRT device.